2007
DOI: 10.1007/s11294-007-9092-0
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Gaps within the EU: A Comparison

Abstract: This research investigates socio-economic gaps between countries of the European Union (EU). The countries, for comparison purposes, are grouped into five sets to find out if the different groupings differ in means and variances. The overall conclusion is that the 15 core combinations outperform the rest when comparisons are made on the basis of 45 socio-economic variables. However, the newly added countries in the enlargement appear to be fairly homogeneous when compared in accordance with the 45 variables. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…An essential finding of this study confirmed the link between social welfare convergence, institutional convergence and convergence of other structural factors. Niroomand and Nissan, (2007), Migala-Warchol & Pasternak-Malicka, (2018) found the convergence of social parameters of development particularly relevant in choosing the direction and social policy tools. Smirnov et al, (2019) investigated the convergence of the socio-economic security indicator in the municipalities of Latvia and its constituents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An essential finding of this study confirmed the link between social welfare convergence, institutional convergence and convergence of other structural factors. Niroomand and Nissan, (2007), Migala-Warchol & Pasternak-Malicka, (2018) found the convergence of social parameters of development particularly relevant in choosing the direction and social policy tools. Smirnov et al, (2019) investigated the convergence of the socio-economic security indicator in the municipalities of Latvia and its constituents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This group of countries shows relative homogeneity in terms of sharing the same communist heritage, common experience in establishing and developing a market economy, and in acceding to the European Union (EU): with eight countries joining the EU in 2004, two (Bulgaria and Romania) in 2007 and the last one (Croatia), in 2013. Moreover, all of these countries display relative homogeneity in terms of many socio-economic variables (Niroomand and Nissan, 2007) and have exhibited a tendency to economic convergence over the last two decades (Amplatz, 2003, andMatkowski andPróchniak, 2007). At the same time, however, there are considerable differences between them in their level of development and in the completion of the transition process to a market-led system (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Conditional convergence implies that differences may be permanent due to cross-country structural factors. Sub-Periods: 1995-2007and 2008 Taking into account this perspective, first interesting conclusion from our results is that the process of conditional convergence is more pronounced in new EU member states, and in the EU as a whole compared to the more competitive economies. A second result from the analysis by sub-periods that deserves our attention is that the speed of conditional convergence has increased during the second period for nearly all indicators and groups of countries.…”
Section: Resultsmentioning
confidence: 64%
“…For instance,Niroomand and Nissan (2007) analysed socio-economic gaps between EU countries considering 45 different variables but not simultaneously.…”
mentioning
confidence: 99%